Does the Progressive Personal Income Tax Drives Tax Evasion in Indonesia? - Estri, Retno; Djamaluddin, Sartika (Proceeding UII-ICABE, 2020)
The aim of this research was to determine whether progressive personal income tax had impact on the tax evasion behavior in Indonesia. The research sample used was the tax audit result data of Personal Taxpayer in the whole Indonesia for twelve years. The result of Tobit Model regression analysis with pooled data showed that the application of progressive tariff system was influential on the tax evasion behavior in Indonesia. The change of tax rates policy enforced through the Law of Income Tax No. 36 of 2008 also contributed on the level of tax evasion in Indonesia. Moreover, the socio-economic and demographic factors were also included in the analysis of identified tax evasion. Keywords: Tax Evasion, Personal Income Tax, Progressive Tax Rates